Green Technologies in the Design of Single-Storey Frameworks - Radkevych, Anatolii V.; Bannikov, Dmytro O.; Wu, H.; Lv, R.; Klochko, Leonid I. (Dnipro University of Technology, Dnipro, 2025)
ENG: Purpose. Analysis of the effectiveness of long-span structural systems based on glued laminated timber for a single-storey frame of a public building. Methodology. The study used a set of research methods, including scientific analysis and synthesis of available technical information on the use of modern wood products for the design of load-bearing frames of buildings with large spans. Computer modelling methods based on the numerical method of structural mechanics – the finite element method – were also used. The analysis of the structural options was performed using the finite element method using the SCAD (Ukraine) design and computing complex. A separate area of work involved design development, which included methods of engineering assessment of the accuracy and reliability of the results obtained, as well as the execution of design documentation. Findings. For the considered structural variants of the equipment compartment frame covering, stress-strain state patterns, as well as natural frequency spectra and vibration modes, were obtained. The structural variant of the frame recommended for practical implementation is based on the set of technical and economic indicators involves the use of an arched covering system. It is also shown that the use of biocomposite glued beams opens up reserves for reducing the material consumption of the structure by preliminary estimates up to 25 %. Originality. The conducted research studies allowed estimating in complex the static and dynamic load-bearing capacity of a large-span frame using glued laminated timber. The high efficiency of the combined frame system, especially in the case of biocomposite timber, has been proven. The obtained frequency spectrum is discrete and lies in the lower frequency range of 1.5‒5.0 Hz. Practical value. The use of glued and biocomposite timber beams for load-bearing elements of single-storey frames opens up a direction of green technologies for specialized buildings, such as a Fire Station. In combination with modern finishing materials such as fire-resistant wood wool, this allows increasing the operational qualities of wooden structures.

UKR: Мета. Аналіз ефективності великопрольотних конструктивних систем на основі клеєного деревного бруса для одноповерхового каркасу громадської будівлі. Методика. У роботі використовувався комплекс методів дослідження, що включає науковий аналіз і синтез наявної технічної інформації стосовно застосування сучасних виробів із деревини для проєктування несучих каркасів будівель із великим прольотами. Також застосовувалися методи комп’ютерного моделювання на базі чисельного методу будівельної механіки – методу скінчених елементів. Аналіз роботи конструктивних варіантів проводився із використанням проєктно-обчислювального комплексу SCAD (Україна). Окремим напрямом у роботі були конструкторські розробки, що включали методи інженерної оцінки точності й достовірності отриманих результатів, а також виконання конструкторської документації. Результати. Для розглянутих конструктивних варіантів покриття каркасу апаратного відсіку отримані картини напружено-деформованого стану, а також спектри власних частот і форм коливань. Рекомендований до практичної реалізації за сукупністю техніко-економічних показників конструктивний варіант каркасу передбачає використання аркової системи покриття. Також показано, що застосування біокомпозитного клеєного бруса відкриває резерви для зниження матеріаломісткості конструкції за попередніми оцінками до 25 %. Наукова новизна. Проведені дослідження дозволили комплексно оцінити статичну й динамічну несучу здатність великопрольотного каркасу із використанням клеєного брусу. Доведена висока ефективність застосування комбінованої системи каркасу, особливо у випадку біокомпозитного брусу. Отриманий частотний спектр при цьому є дискретним і лежить у діапазоні нижніх частот 1,5‒5,0 Гц. Практична значимість. Використання для несучих елементів одноповерхових каркасів клеєного й біокомпозитного деревних брусів відкриває напрям «зелених» технологій для будівель спеціалізованого призначення, таких як Пожежна станція. У сукупності із сучасними оздоблювальними матеріалами типу вогнестійкої деревної шерсті це дозволяє підвищити експлуатаційні якості дерев’яних конструкцій.
«Зелені» технології у проєктуванні одноповерхових каркасів
А. Radkevych: ORCID 0000-0001-6325-8517; D. Bannikov: ORCID 0000-0002-9019-9679; H. Wu: ORCID 0000-0003-0857-6883; R. Lv: ORCID 0009-0000-6906-7578; L. Klochko: ORCID 0009-0009-3478-6076
Keywords: wood; glued laminated timber; biocomposite laminated timber; load-bearing framework; equipment compartment; деревина; клеєний деревний брус; біокопозитний деревний брус; несучий каркас; апаратний відсік; КБВ; TECHNOLOGY::Other technology::Environmental engineering